SETS-based guided experiment book: Empowering science process skills of elementary school students - Prasasti, Pinkan Amita Tri; Listiani, Ivayuni (University of Muhammadiyah Malang, 2018)
In this 21stâcentury, students are expected to have current competencies in which one of them is science process skills. The aim of this research was to empower science process skills through the SETS-based guided experiment book. This Posttest Only Control Group Design study involved 50 students of fifth grade which divided into two groups i.e. 25 students as the experimental group and 25 students as the control group. The activities were carried out for three months outside of school. The empowerment of science process skills was measured from the increasing scores before and after the implementation of the SETS Guided Experiment Book. The results showed that there was a significant different between experimental group and control group as the significancy value was 0.01 (sig. < 0.05). This means that the SETS-based guided experiment book can empower Science process skill of elementary school students.